âAT LEAST, I HAVE TO REPEAT FIVE TIMESâ FREQUENT READING DIFFICULTIES - Mutia Ismail, Nyak (STKIP Bina Bangsa Getsempena Banda Aceh, 2017)
PISAâs result in 2016 shows that Indonesian country score in reading, 397, is still below PISA average score, 493. Although the rank increased, the below-average score denotes that the students are still less literate while reading is vital to all scholars. Most higher education students still encounter difficulties when reading, per se reading is profoundly essential in academes. This study is devoted to shed light on intrapersonal difficulties that higher students face in reading. Qualitative research method was employed involving 83 Economics students at Syiah Kuala University. The data collection process was carried out through questionnaire and interview procedures after which the data were analyzed using three-steps analysis. The result suggests that 91.5% of the students has difficulties in retentionâwhere they tend to fail retrieving just-obtained information, discharge information found in passage(s) with prior knowledge, and cannot relate the information with real life experiences. Then 87% has comprehension difficulty where they are not optimally engaged while reading, confused with contextual meanings, main ideas and supporting details, and about what to expect from passage(s). Finally, 12% faces problems in decoding (regardless of Dyslexic symptoms) for which they still read word-by-word and occasionally despise punctuations. Generally, it leads to a discussion that problems in concentrating promote problems in memory-processing. The authors would gently suggest students to be trained to monitor and regulate their metacognitive ability during reading.Keywords: Reading Difficulties, Retention, Comprehension, Decoding, Memory-Processing.